Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1975
DOI: 10.1136/jcp.28.10.814
|View full text |Cite
|
Sign up to set email alerts
|

Platelet aggregability in relation to impaired consciousness after head injury.

Abstract: SYNOPSIS ADP-induced platelet aggregation was studied for up to six weeks in 34 patients with head injuries. The patients were divided into three groups according to the degree of impaired consciousness assessed by a clinical coma scale, and change in platelet aggregation was related to the coma score. Platelet aggregation was markedly reduced in all eight patients dying within 24 hours of injury. All 17 patients who remained unconscious for four days or more showed decreased platelet aggregation up to nine da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The methods used were TEG, Multiplate® (Roche Diagnostics, Basel, Switzerland) and spectrophotometry. All studies found that platelet function decreased after injury [ 22 , 24 , 29 , 36 38 ]. This appeared to be independent of platelet transfusion and pre-injury antithrombic therapy [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods used were TEG, Multiplate® (Roche Diagnostics, Basel, Switzerland) and spectrophotometry. All studies found that platelet function decreased after injury [ 22 , 24 , 29 , 36 38 ]. This appeared to be independent of platelet transfusion and pre-injury antithrombic therapy [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five other studies reported a similar pattern of normal to below-normal platelet function on admission that then decreased over time in stimulation to collagen (COL) [ 24 ], ADP, thrombin receptor activating peptide (TRAP) and arachidonic acid (AA or ASPI) [ 22 , 37 ]. The lowest platelet function levels were observed 6–48 h after injury [ 24 , 29 , 37 , 38 ] and then returned to normal after 2–16 days [ 22 , 29 , 37 , 38 ]. In the two studies that observed patients for more than one week, platelet function increased to above-normal levels (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet count also follows similar pattern albeit slowly [80] though onset of recovery occurs earlier than platelet functions [128] that correlates with changes in ADAMTS-13 levels [130]. The trend of initial hypofunction followed by restoration and rebound hyperfunction has been observed in diverse conditions such as head injury [93,121,131], critical care units [24], and spinal cord injury [132]. In an animal model of TBI, the changes paralleled increase in pro inflammatory cytokines such as IL-6, KC (keratinocyte chemoattractant), and soluble p-selectin [133].…”
Section: Time Course Of Platelet Function In Traumamentioning
confidence: 84%
“…The tissue factor-factor VII complex activates factor X and prothrombin, occasionally leading to DIC with consequent hemorrhage. Apart from DIC, other coagulation abnormalities like thrombocytopenia and platelet function disorders have been reported to occur commonly following head injury 13 .…”
Section: Pathophysiologymentioning
confidence: 99%